Back Cover: Encoding Multilayer Complexity in Anti‐Counterfeiting Heterometallic MOF‐Based Optical Tags (Angew. Chem. Int. Ed. 3/2021). Issue 3 (15th December 2020) - Deneff, Jacob I.; Butler, Kimberly S.; Rohwer, Lauren E. S.; Pearce, Charles J.; Valdez, Nichole R.; Rodriguez, Mark A.; Luk, Ting S.; Sava Gallis, Dorina F.
Abstract : Heterometallic rare‐earth metal–organic frameworks based on nonanuclear metal clusters were implemented as highly intricate optical tags, as described by Dorina F. Sava Gallis and co‐workers in their Research Article on page 1203 . Subtle compositional changes have a pronounced effect on intermetallic energy transfer, and thus on the resulting photophysical properties. Concomitant multi‐emissive spectra and luminescence lifetimes result in tags with both overt (visible) and covert (near‐infrared) properties, authenticated using orthogonal detection methodologies.